Wildlife of Florida Factsheets: Florida Sandhill Crane - Hannah Fox; Bethany Rose Wight; Hance Ellington Ellington (EDIS)
Learn more about Florida Sandhill Cranes! The Wildlife of Florida Factsheet series was created to provide the public with a quick, accurate introduction to Florida’s wildlife, including both native and invasive species. We hope these fact sheets inspire people to investigate wildlife in their own backyards and communities and understand the amazing biodiversity of wildlife in the state of Florida—in this case, the sandhill crane.